Otimização da sensibilidade de sensores ópticos de índice de refração baseados em guias de onda - Duarte, Lucas Eduardo Ribeiro (2021)
The growing demand for optical detection platforms that are reliable, yet easy to use and compact, which require low sample consumption and provide high sensitivity and real-time monitoring, have brought about considerable innovations in the design of optical sensors in recent years. Among them, the waveguides that use the detection scheme based on intensity stand out. These devices have been objects of great scientific interest, as they provide high sensitivity and simplicity in the detection scheme. With the advancement of nanofabrication techniques, the development of optical sensors based on waveguide nanostructures has represented an excellent way to integrate them into platforms known as a lab-on-a-chip. In this context, a refractive index sensor based on the intensity detection is proposed and numerically simulated. The proposed sensor is composed of a structure with a tapered waveguide of silicon nitride on a glass substrate, integrated with a sensing window. The tapered waveguide design aims to expand the interaction area of the evanescent field with the analyte, increasing the device sensitivity. In order to verify the sensor performance and provide a high fidelity numerical simulation, a 3D semi-vectorial beam propagation method is employed. Both bulk and surface maximum sensitivity was computed and the values 1701 %/RIU and 1.74 %/nm were obtained, respectively. The results suggest that the proposed sensor can detect a significant change on the refractive index and the layer thickness of a protein on aqueous solutions. Finally, the present investigation proposes an optical device that is compact, structurally simple and provides high performance for biochemical analysis.